Digital Literacy Bullying Prevention Efforts for Students - M. Fakhrurrozy K.; Lubis, M. Joharis; Hutagalung, Surya Masniari (International Journal of Educational Research Excellence (IJERE), 2025)
Bullying remains a pressing issue in schools worldwide. To address this problem, we developed an innovative e-module that integrates storytelling, digital literacy, and interactive activities to prevent bullying among middle and high school students. This study evaluated the effectiveness of the e-module in fostering empathy, promoting digital citizenship, and equipping students with strategies to respond to bullying. Results indicated a significant increase in students' knowledge about bullying, their ability to identify different forms of bullying, and their confidence in reporting incidents. Additionally, the e-module was found to be highly engaging and enjoyable for students. These findings suggest that the e-module is a promising tool for schools seeking to create safer and more inclusive learning environments